Behavior dynamics in media-sharing social networks - Zhao, H. Vicky; Lin, W. Sabrina; Liu, K. J. Ray (Cambridge ; New York : Cambridge University Press, 2011)
"In large-scale media-sharing social networks, where millions of users create, share, link and reuse media content, there are clear challenges in protecting content security and intellectual property, and in designing scalable and reliable networks capable of handling high levels of traffic. This comprehensive resource demonstrates how game theory can be used to model user dynamics and optimize design of media-sharing networks. It reviews the fundamental methodologies used to model and analyze human behavior, using examples from real-world multimedia social networks. With a thorough investigation of the impact of human factors on multimedia system design, this accessible book shows how an understanding of human behavior can be used to improve system performance. Bringing together mathematical tools and engineering concepts with ideas from sociology and human behavior analysis, this one-stop guide will enable researchers to explore this emerging field further and ultimately design media-sharing systems with more efficient, secure and personalized services"--
Includes bibliographical references (p. [326]-334) and index.
Keywords: Social networks; Consumer behavior; Human behavior; Game theory